Analysis Study of the Effect of Entrepreneurial Innovation on Customer Satisfaction and Purchase Intention - Suryawan, Teguh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Many factors influence the demand for products, and researchers around the world have difficulty defining an effective and comprehensive theoretical framework that can be easily applied to the factors that motivate the demand for new products. The research method used in this study uses a systematic literature review method. While business innovation can attract consumers, innovation makes consumers interested in products that have just been sold or sold, this kind of innovation makes customer satisfaction higher than before when products sold have not been sold or are in the factory. Stage, it is better to do a test before, and If the consumer considers it acceptable then the innovation can continue. The results of this study found that innovation has a significant impact on entrepreneurship, especially improving purchasing power and customer satisfaction.